Young guns II - Estevez, Emilio, 1962-; Sutherland, Kiefer, 1967-; Phillips, Lou Diamond, 1962-; Slater, Christian; Murphy, Geoff, 1935-; Morgan Creek Productions; Twentieth Century-Fox Film Corporation; Fox Video (Firm) (Beverly Hills, Calif. : Warner Home Video, 1999)
Following the Lincoln County Wars, Billy the Kid has lost power to the ruthless cattle barons and crooked lawmen. Pat Garrett has been hired to bring Billy to justice, so Billy joins his outlaw pals to battle the lynch mobs and gunslingers.
Videocassette release of the 1990 motion picture.
"17246"-container.
Songs by John Bon Jovi ; music by Alan Silvestri ; editor Bruce Green ; production designer Gene Rudolf ; director of photography Dean Semler ; co-executive producers David Nicksay and Gary Barber ; executive producers James G. Robinson, Joe Roth, and John Fusco ; written by John Fusco ; produced by Paul Schiff and Irby Smith ; directed by Geoff Murphy.
Emilio Esteves, Kiefer Sutherland, Lou Diamond Phillips, Christian Slater.
MPAA rating: PG-13.
VHS format. Hi-fi stereo. First quality SP. Dolby.
Keywords: Western films; Films for the hearing impaired; Feature films